2021
DOI: 10.1136/bmjgh-2021-005223
|View full text |Cite
|
Sign up to set email alerts
|

A partisan pandemic: state government public health policies to combat COVID-19 in Brazil

Abstract: IntroductionTo present an analysis of the Brazilian health system and subnational (state) variation in response to the COVID-19 pandemic, based on 10 non-pharmaceutical interventions (NPIs).Materials and methodsWe collected daily information on implementation of 10 NPI designed to inform the public of health risks and promote distancing and mask use at the national level for eight countries across the Americas. We then analyse the adoption of the 10 policies across Brazil’s 27 states over time, individually an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
1
45
0
6
Order By: Relevance
“…For its second dose, it was observed that healthcare workers remained leading in clusters of low VR in Brazil. This event was due, among other reasons, to the period covered by the study and to political and institutional disagreements [ 42 44 ], which ended up putting scientific negationism and ideological aspects ahead of vaccination objectives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For its second dose, it was observed that healthcare workers remained leading in clusters of low VR in Brazil. This event was due, among other reasons, to the period covered by the study and to political and institutional disagreements [ 42 44 ], which ended up putting scientific negationism and ideological aspects ahead of vaccination objectives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to its continental dimensions and with multiple points of tension outside the political arena, Brazil needed to seek very efficient and coordinated logistical solutions for distribution and storage. In this sense, small failures accumulated throughout the process ended up causing delays and losses during the stages of immunisation, making the country quickly susceptible to the enormous human and material impacts of the pandemic during almost the entire year of 2020 [ 42 44 ]. This occurrence can be verified in the vaccination proportional to the population ranking [ 45 ], in which Brazil ranked 78th at the beginning of June 2021.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At subnational level, all Mexican states implemented (at variable timing) these mitigation strategies, 13 and compared to other Latin American countries, Mexico and Brazil showed a delayed response after the first confirmed case. ( Touchton et al, 2021 )…”
Section: Introductionmentioning
confidence: 99%